Professional compatibility for a sample of the winners of Prince Fahd bin Sultan’s award and its relationship with the ambition in light of some different demographic variables - Al-atawi, Atallah Mohammad (Journal of Educational and Psychological Sciences, 2020)
The current study aimed to ascertain the level of professional compatibility for a sample of the winners of Prince Fahd bin Sultan and its relationship with the ambition regarding some demographic variables. To achieve the objective of the study، a sample consisted of male and female 23 individuals of the winners of Prince Fahd bin Sultan’s award were chosen from the winners over several years. Two scales were developed; the scale of professional compatibility and the scale of ambition. Psychometric properties of both scales were verified، including validity and reliability. The study found that the level of professional compatibility and ambition of the study sample was high and that there was a positive correlation between professional compatibility and ambition. It was also found that professional compatibility and ambition had no difference in regard to gender، age، educational level، year of award، current profession and the reason behind being awarded. Depending on the study results، some recommendations were stated including the need to work on and grant a variety of different awards as well as the involvement of award winners in activities that serve the community.